Projected sensitivities of the LUX-ZEPLIN experiment to new physics via low-energy electron recoils - Akerib, DS; Al Musalhi, AK; Alsum, SK; Cottle; Fearon, NM; Gibson, E; Kraus, H; Palladino, KJ; Stevens, A; Et al. (American Physical Society, 2021)
LUX-ZEPLIN is a dark matter detector expected to obtain world-leading sensitivity to weakly-interacting massive particles interacting via nuclear recoils with a ∼7-tonne xenon target mass. This paper presents sensitivity projections to several low-energy signals of the complementary electron recoil signal type: 1) an effective neutrino magnetic moment, and 2) an effective neutrino millicharge, both for pp-chain solar neutrinos, 3) an axion flux generated by the Sun, 4) axionlike particles forming the Galactic dark matter, 5) hidden photons, 6) mirror dark matter, and 7) leptophilic dark matter. World-leading sensitivities are expected in each case, a result of the large 5.6 t 1000 d exposure and low expected rate of electron-recoil backgrounds in the <100 keV energy regime. A consistent signal generation, background model and profile-likelihood analysis framework is used throughout.